Phytochemical screening, isolation, antibacterial and anticancer activity studiesof caesalpinia pulcherrima Linn leaves by HPTLC analysis - ANJU.V,; SUBIN MARY ZACHARIAH, (International Journal of Pharma and Bio Sciences, 2017)
Caesalpinia pulcherrima Linn commonly known as peacock flower belonging to family Caesalpiniaceae is an ornamental plant widely distributed in Asia. The plant and its parts are widely used in traditional medicine for the treatment of various disorders. The aim of the work was to study the pharmacological activities of the leaf extract and isolated fractions. Preliminary phytochemical analysis was carried out to determine the constituents present in different extracts of plant. The methanolic extract showed maximum active constituents and their quantitative determination were carried out and matches with their standards. The TLC and HPTLC analysis of the methanolic extract for determination of major phytoconstituents were carried out. Further isolation of the total flavanoid and phenolic fraction were done using suitable solvent systems. The methanolic extract and isolated fractions were tested for their antibacterial, invitro antioxidant and anticancer activities. The antibacterial activity was carried out using agar well diffusion method and the MIC was determined using broth dilution method. The invitro antioxidant assay were carried out by different methods. The invitro anticancer activity of the extract and fractions were carried out in HepG2 cell line using MTT assay .The results showed that Caesalpinia pulcherrima leaf constituents showed good anticancer activity.